2010
DOI: 10.1039/c0ce00105h
|View full text |Cite
|
Sign up to set email alerts
|

N,N′-Dihexylbenzimidazolium salts. Anion-controlled bilayer structures viaπ–π dimer or C–H⋯π catemer motifs

Abstract: A series of N,N 0 -dihexylbenzimidazolium salts with three anions, Br À , I À and PF 6 À , have been synthesized and characterized by single-crystal X-ray diffraction. These salts exhibit some anionindependent structural properties, which include the U-shaped conformation, the interdigitated bilayer packing and the thickness of the ionic layer. These salts also show anion-controlled inter-headgroup interactions; the benzimidazolium headgroups form a dimer motif via p-p interaction when the anions are Br À and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…43 The experimental setup prepared for the gas sensor testing system is suitable to determine the sensitivity parameter mainly the response time and recovery time of the fabricated 4i gas sensor detector. It consists of a cylindrical stainless-steel test chamber with an effective volume of 2649 cm 3 , and it has an inlet for permitting the tested gas to ow in and an air admittance valve to permit the ow of atmospheric air aer evacuation. The hotplate and K-type thermocouple were placed inside the chamber to control the operating temperature.…”
Section: Sensor Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…43 The experimental setup prepared for the gas sensor testing system is suitable to determine the sensitivity parameter mainly the response time and recovery time of the fabricated 4i gas sensor detector. It consists of a cylindrical stainless-steel test chamber with an effective volume of 2649 cm 3 , and it has an inlet for permitting the tested gas to ow in and an air admittance valve to permit the ow of atmospheric air aer evacuation. The hotplate and K-type thermocouple were placed inside the chamber to control the operating temperature.…”
Section: Sensor Testingmentioning
confidence: 99%
“…It has been shown that imidazolium and benzimidazolium salts are important in the eld of ionic liquids (IL) and ionic liquid crystals (ILCs). [1][2][3][4][5][6][7] A large number of these types containing imidazolium and benzimidazolium units have hitherto been synthesized and their application has been studied in liquid crystals, 8 sensing, 9,10 anticancer and other applications. [11][12][13][14][15][16][17] Among an enormous variety of ionic mesogens studied so far, majority is derived from imidazolium cations.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent examples highlighting the importance of CH/π in stabilising their crystal structures include N,N -dihexylbenzimidazolium salts [78], copper complexes of a pyrimidine ligand [79], tris(1-organo-imidazol-2-ylthio)methane [80], 1-formyldipyrromethanes [81], an alkynyl-substituted ferrocene [82], a zinc porphyrin-1,2-3-triazole conjugate [83], a dicyclopentadienylaluminum complex [84], 3-sec-butyl-2,3-dihydro-1H-(isoquinolin-4-ylidene)acetic acid [85], a silver complex [86], 3,4-dichloro-2 ,4,6 -triethylbenzophenone [87], hexaaryltriindoles [88], a pyrazolo [3,4-d]pyrimidine [89], [Ru(η 6 -bip) 2 ] +2 , [Os(η 6 -bip) 2 ] +2 (bip is biphenyl) [90], [(Ph) 4 As] + [Co(NCS) 2 Cl 2 ] 2− [91], a dinuclear aluminium complex containing two pyrazole groups [92], N-(5-ethyl- [1,3,4]-thiadiazole-2-yl)toluenesulfonamide [93], trimetallo-macrocycles with naphthanoimidazolate and benzoimidazolate anions [94]. …”
Section: Crystal Packingmentioning
confidence: 99%